Pengaruh Push, Pull, dan Mooring terhadap Switching Intention pada Konsumen Pengguna Wifi di Era Pandemi Covid-19 - Adita Primadana Sugandha; Tias Andarini Indarwati (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
Internet use during the current pandemic is increasing, and most are done online. Work From Home (WFH) and School From Home (SFH) require stable and smooth internet. In addition to the internet, smartphones also play an essential role in people's daily lives during restrictions due to the pandemic. This study aims to analyze and discuss the effect of push, pull and mooring on switching intention. This study uses a push-pull-mooring model with an approach through switching intention. Respondents in this study were at least 20 years old. Due to this age, respondents have entered the adult stage in switching intentions from internet data packages to wifi. The sample used is 110 respondents—the sampling method used non-probability sampling with the judgmental sampling method. The analysis technique uses multiple linear regression with SPSS26 software. Based on the results obtained, it is known that the push variable on switching intention to use wifi has a positive effect. The pull variable has a positive impact on switching intention to use wifi. When the push and pull are getting stronger, consumers will switch. Mooring variable does not affect internet data packet switching intention to private wifi. This result shows that the switching intention of data packets to use wifi privately at home is relatively high. Due to using private wifi, you can access or surf the internet at a stable speed compared to data packet internet, in contrast to using data packet internet whose network is unstable.